PENGARUH ATRIBUT PRODUK TERHADAP LOYALITAS KONSUMEN BLUE BAND DI MEDAN JOHOR - Pinem, Laura Juita (Agriprimatech, 2023)
The purpose of this research is to examine the influence of attributes found in Blue Band margarine products on consumer loyalty towards margarine. The attributes to be analyzed in this study are brand image, taste, packaging, and nutritional content. The respondents consist of 100 housewives from the Medan Johor District. The sample was drawn from the population based on calculations using the Slovin method. Data obtained from the respondents were then analyzed using multiple linear regression with the use of SPSS software. The data processing results show that all four independent variables, namely brand image, taste, packaging, and nutritional content, affect respondent loyalty. Keywords: margarine, loyalty, brand, packaging, regression, Blue Band.